Hukum Islam Indonesia sebagai Role Model Islam Nusantara - Kasjim Salenda (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
This paper analyzes the distinction of Islamic law in Indonesia as a role model of Indonesian Islam (Islam Nusantara). The underlying question is that what are the disticntions of Indonesian Islamic law which can be a role model for Indonesian Islam. The purpose of this paper is to identify the characteristics of Islamic law in Indonesia as well as to elaborate the distinctiveness of Indonesian Islam as a role model. It is showed that Islamic law in Indonesia has been well integrated into Indonesian culture and Indonesian legislations. Indonesian Islam (Islam Nusantara) initiated by Nahdatul Ulama shows its capacities to accommodate local wisdom (culture) and Islamic law, so that there is no conflict among them. It is peaceful, pluralistic and egalitarian approach, and there will be ‘role model’ for Islamic civilization.